Urgensi Guru Pendidikan Agama Islam Dalam Pembentukan Akhlak Siswa Di Era Digitalisasi : Studi Kasus di SDN Mayangan 2 Kota Probolinggo - Moch. Salman Alfarizi; Benny prasetiya; Subhan Adi Santoso (Jurnal Pendidikan Islam, 2023)
Interests from social media and online games are now in demand by minors and teenagers/puberty, not something new when you pay attention to those who always play their respective cellphones. From this phenomenon, it will be very far left behind in the aspects of education and morals if you are still unable to use this technology that requires an internet connection. PAI teachers have a big role in fostering student morals in the digitalization era.The purpose of this research is to find out how the role of PAI teachers in fostering student morals in the digitalization era at SDN Mayangan 2. Based on the methods and types of facts used, this research was conducted with qualitative research methods so that it would produce descriptive information in word structure. The statistics analyzed in it are in a descriptive structure, no longer numbers as is the case in quantitative research. The result of this research is that the role of PAI teachers in moral development is very important for the moral development of students at SDN Mayangan 2. The efforts that have been made by PAI teachers at SDN Mayangan 2 are to provide an understanding of morality by providing examples and also by strengthening faith. by getting closer to Allah Subhanahu Wa Ta'ala by diligently praying and also diligently reading the Koran. Morals are very important in the era of digitalization so that students can control themselves so they don't easily fall into the negative impacts resulting from technological developments and also improve students' morals on the use of social media such as Tik Tok and also self-control so that students take advantage of social media more . Supervision of a teacher to his students in the use of developmental technology is very important. The challenges felt by the teachers at SDN Mayangan 2 in terms of fostering students' morals are the lack of cooperation between the school and also the parents, the lack of support from parents and also the lack of collaboration between parents and the school, as well as other influences. from the community such as friendship or miscommunication, and the last is the limited time in school so that moral development efforts cannot run fully.